Exploring the Challenges of Implementing OECD Due Diligence Practices in Supply Chains: Effects on Sustainability in Emerging Economies - Siraj, Md. Tanvir; Talukdar Tonmoy, Md. Faiaz Arman; Arman, S M Shahrukh; Zaman, Monabbir E; Saeed, Syed Salman; Rahaman, Mahbubur (Optimality, 2025)
Adopting the Organization for Economic Cooperation and Development (OECD) due diligence practices in supply chains is crucial for ensuring ethical, transparent, and sustainable business operations, particularly in emerging economies. However, various socio-economic and institutional challenges hinder the effective implementation of these practices. Therefore, this study aims to identify and prioritize the key challenges faced in adopting OECD due diligence within the supply chains of emerging economies. In this study, Multi-Criteria Decision-Making (MCDM) techniques, including the Analytic Hierarchy Process (AHP), the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE), were applied. The integrated combinations of AHP-TOPSIS and AHP-PROMETHEE were used to verify the robustness of the study results. The study reviewed the literature to identify the prioritization criteria and challenges, and also incorporated expert input. This study selected six criteria and seventeen challenges. AHP determined ‘Severity of Impact’ and ‘institutional and regulatory’ as the most influential criteria. ‘Weak regulatory enforcement,’ ‘corruption and governance issues,’ and ‘political instability’ were identified as the top three challenges in both the AHP-TOPSIS and AHP-PROMETHEE approaches. By addressing these challenges, policymakers and industry leaders can foster a more resilient and responsible supply chain ecosystem in emerging economies. This study provides strategic insights to enhance regulatory effectiveness, stakeholder collaboration, and institutional capacity, ultimately facilitating the successful adoption of OECD due diligence guidelines.